2020
DOI: 10.1002/leap.1339
|View full text |Cite
|
Sign up to set email alerts
|

The relationship and incidence of three editorial notices in PubPeer: Errata, expressions of concern, and retractions

Abstract: This article studies the incidence and relationship of three important relevant editorial notices: errata, expressions of concern, and retractions.The journal club PubPeer was used to extract 39,449 research articles and the 2,308 errata, 189 expressions of concern, and 1,531 retractions associated with these publications. The relationship, time delay, and evolution of these publications were then compared, as was their incidence in journals and disciplines. The results show that the relationship between them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
7
0
2
Order By: Relevance
“…Specifically, Immunology and Microbiology , Biochemistry , Genetics and Molecular Biology , and Pharmacology , Toxicology and Pharmaceutics receive the most comments about publishing fraud and data manipulation. This result coincides with previous studies about the disciplinary distribution of retractions (Ortega, 2020; Tripathi et al, 2019) and highlights the great problem of image manipulation in Biomedicine today (Bik et al, 2016; Oksvold, 2015). Otherwise, social science and humanity disciplines indicate a high proportion of comments about critical reviews and methodological flaws, which exposes the importance of theoretical discussion in the humanities and the misuse of statistical methods in the social sciences (Brown & Hedges, 2009; Lamiell, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Specifically, Immunology and Microbiology , Biochemistry , Genetics and Molecular Biology , and Pharmacology , Toxicology and Pharmaceutics receive the most comments about publishing fraud and data manipulation. This result coincides with previous studies about the disciplinary distribution of retractions (Ortega, 2020; Tripathi et al, 2019) and highlights the great problem of image manipulation in Biomedicine today (Bik et al, 2016; Oksvold, 2015). Otherwise, social science and humanity disciplines indicate a high proportion of comments about critical reviews and methodological flaws, which exposes the importance of theoretical discussion in the humanities and the misuse of statistical methods in the social sciences (Brown & Hedges, 2009; Lamiell, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…More recently, Bordignon (2020) used PubPeer comments to test the influence of negative comments in the retraction/correction of papers, concluding that PubPeer contributes more to the correction of science than negative citations. Ortega (2020) studied the incidence of editorial notices in PubPeer, observing that editorial notices are more common in multidisciplinary journals and those specializing in biochemistry and medicine. Other publications only focused on theoretical discussions about the problem of anonymity and the implications of post‐publication review (Blatt, 2015; Teixeira da Silva, 2018; Torny, 2018; Townsend, 2013).…”
Section: Related Researchmentioning
confidence: 99%
“…Cox et al (2018) found that 51% of 55 RNs in the field of economics published by some leading publishers did not indicate the reason for retraction, even though the journals claimed to follow COPE retraction guidelines, including the requirement to clearly state the reason for retraction. They also noticed that the time between the detection of the retraction‐inducing issue and the retraction itself could take years, with 20% of their studied retractions taking 3 years to complete, a finding that Ortega (2021) also observed using PubPeer‐based data.…”
Section: Opacity In Rnsmentioning
confidence: 78%
“…Estas notas editoriales son principalmente erratas, expresiones de preocupación y retractaciones. PubPeer indica cuando una publicación ha sido sujeto de una nota editorial (Ortega, 2021). Sin embargo, se desconoce la capacidad de esta plataforma para detectar cuándo se publica una nota editorial y luego se asocia a una publicación.…”
Section: Cobertura De Notas Editorialesunclassified
“…Otra importante limitación es la lentitud de las acciones editoriales, que podrían retrasar la emisión de notas editoriales (Stricker;Günther, 2019;Ortega, 2021). Este problema causa que algunas publicaciones recientes que podrían merecer una nota editorial, estarían bajo investigación.…”
Section: Limitacionesunclassified